Lydia Williams, Oral History Interview, July 24, 2025 - Lydia Williams (Valdosta State University Archives and Special Collections, 2026., 2025)
Lydia Williams discusses her lifelong connection to River Hill Missionary Baptist Church, sharing memories of faith, family, community traditions, and the church’s role in shaping her values. She reflects on growing up during school integration, her activism, and her career in social services and advocacy. Williams emphasizes the importance of preserving African American history, protecting the church’s legacy, and passing community stories to future generations.
1 audio file (MP3) and 1 transcript PDF/A.
Keywords: River Hill Missionary Baptist Church (Valdosta, Ga.); Oral history; Baptist church buildings; Baptists; African American churches